Perancangan Sistem Informasi Persediaan Alat Tulis Kantor Berbasis Web - Ita Erliyani; Winda Afriandini; Titys Wicaksono Wibowo (IJAcc, 2021)
The 4.0 revolution that is taking place also moves, not only about the Revolution in the industrial field but also in the information field. Decision making to regulate the Office Stationery system. Especially the office stationery inventory system plays an important role in the process of procuring office stationery in the RSUP. Dr.Salala in the field of inventory, provides information about inventory reports that are still manual for requests for office stationery. The purpose of this study is to design a system that can provide updated information and make it easier for users to submit requests for goods. In this study, the authors used the PIECES analysis method, the analysis method for the Unified Modeling Language (UML) program, designed using the PHP (Hypertext Preprocessor) programming language, and with the MySql database. This is the rationale for how the authors analyze the procurement system in RSUP. Dr. Salala can facilitate the inventory of goods requested for effective and efficient reporting.